ARE WE SISYPHI? Reflections on the Meaning of Life - Pobojewska, Aldona (Hybris, 2020)
We are now more often than ever contemplating existential problems. In this text I present some reflections related to the issue in the title. I do it in two steps. First, I consider from which perspective one can reasonably and effectively adjudicate about the meaning of an individual's life. Next, I illustrate this problem by presenting several concepts that refer to the mythological fate of Sisyphus. I precede the text with an introduction and close with an ending.